Meningkatkan Hasil Belaar PAK Melalui Media Video Pembelajaran - Sitanggang, Martina (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This research was conducted at SD Negeri 064983 Medan. The research method uses Classroom Action Research with three cycles. This study was designed to last for 3 months. Based on the discussion of the results of the study, several conclusions can be drawn, namely in the initial test before the action was given that the class average score was 70.58 and the percentage of classical completeness was only 25%. In the first cycle of action with the application of the media method The learning videos obtained the class average value of 77.58, the percentage of classical completeness of 50% and the value of student activity observations, this indicates an increase from the initial test in terms of class average and learning completeness. In the second cycle of action by applying the instructional video media method, it was found that the class average score increased until it reached 84.43 and the student's observation value increased to reach 85%. By applying the instructional video media method, it can improve student learning outcomes in the material I am grateful for as a woman or a boy in 4 SD N 064983 Medan for the 2020/2021 academic year. Keywords: be grateful; gender; instructional video media  Abstrak: Penelitian ini dilaksanakan di SD Negeri 064983 Medan. Metode penelitian menggunakan metode Penelitian Tindakan Kelas dengan tiga siklus. Penelitian ini dirancang berlangsung selama 3 bulan.Berdasarkan dari pembahasan hasil penelitian maka dapat ditarik beberapa simpulan yaitu Pada tes awal sebelum diberikan tindakan bahwa nilai rata-rata kelas 70,58 dan jumlah persentase ketuntasan klasikal hanya 25% Pada tindakan siklus I dengan penerapan metode media video pembelajaran diperoleh nilai rata-rata kelas 77,58  persentase ketuntasan klasikal 50% dan nilai observasi aktivitas siswa hal ini menunjukkan adanya peningkatan dari tes awal dari segi rata-rata kelas maupun ketuntasan belajar. Pada tindakan siklus II denagan penerapan metode media video pembelajaran diperoleh nilai rata-rata kelas semakin meningkat hingga mencapai 84,43 dan nilai observasi siswa meningkat sehingga mencapai 85%. Dengan penerapan metode media video pembelajaran  dapat meningkatkan hasil belajar siswa pada materi aku bersyukur sebagai perempuan attau laki-laki di 4 SD N 064983 Medan Tahun Pelajaran 2020/2021. Kata Kunci: bersyukur; jenis kelamin; media video pembelajaran